Local value chain interventions: a systematic review. Issue 4 (26th September 2019) - Hainzer, Kirt; Best, Talitha; Brown, Philip Hugh
Abstract : Purpose: The purpose of this paper twofold: first, to review the current state of knowledge regarding local value chain (LVC) interventions in the context of international agricultural research and development; and, secondly, by synthesising the empirical findings from LVC projects, to provide guidance for future research and intervention design. Design/methodology/approach: This paper utilises systematic review and qualitative meta-synthesis guidelines to review and synthesise recent research papers and case studies dealing specifically with the development of LVCs, authored by professionals affiliated with development agencies and international research consortiums. Findings: The paper identifies a novel two-phase characterisation of LVC interventions. Phase 1 identifies opportunities for interventions, which are characterised as typologies and presented upon a spectrum of value chain functionality from underdeveloped to mature. Phase 2 is the selection and implementation of strategies to achieve the identified opportunities from Phase 1, and the paper characterises these strategies per the domain of value chain functionality which they target. Research limitations/implications: The interaction between context, socio-economic constraints and intervention strategies is still a poorly understood feature of value chain interventions, and the paper posits that a greater understanding of these interactions is crucial to the success of value chain interventions. Originality/value: The paper provides the first synthesis of LVC interventions, while outlining research priorities and knowledge gaps required to design interventions which are consummate to the context and functionality of a prioritised chain.